Digital Culture & Society (transcript-Verlag, 2015)
Digital Culture & Society is a refereed, international journal, fostering discussion about the ways in which digital technologies, platforms and applications reconfigure daily lives and practices. It offers a forum for critical analysis and inquiries into digital media theory. The newly established journal provides a publication environment for interdisciplinary research approaches, contemporary theory developments and methodological innovation in digital media studies. It invites reflection on how culture unfolds through the use of digital technology, and how it conversely influences the development of digital technology itself. The journal is a research platform for those who are interested in the interdisciplinary field of digital media studies. It involves topics such as New Materialism, Gamification, Surveillance and Privacy, Big Data, Sensory Ethnography, Quantified Self, Extimacy, and Digital Cartography. This however, is a non-exhaustive list, and new topics will continuously supplement these themes due to the dynamic of the research field. The journal's goal is to create a cross-disciplinary repository on the interconnection between research fields such as media studies, cultural studies, science and technology studies, sociology, gender studies, anthropology, game studies, media/art history and information science.